ESPÉCIES ARBÓREAS INVASORAS NO PAISAGISMO DOS PARQUES URBANOS DE CURITIBA, PR - Biondi, Daniela; Muller, Eduardo (Floresta, 2013)
O objetivo deste trabalho foi caracterizar as espécies arbóreas introduzidas no paisagismo de cinco parques urbanos de Curitiba, principalmente no aspecto relativo às espécies exóticas invasoras. Sortearam-se aleatoriamente cinco parques: Passeio Público, Parque Bacacheri, Parque São Lourenço, Parque Barigui e Parque Municipal do Passaúna. As árvores foram identificadas quanto a taxonomia e origem. Foram analisados 5525 indivíduos arbóreos, sendo identificados 95,9% até o nível de espécie. Da população analisada, foram identificadas 149 espécies e 48 famílias. Apenas 7 famílias representam 50% do total, com predominância de Fabaceae (20,8%), sendo que o maior número de famílias verificou-se no Parque São Lourenço. Quanto à origem, 38,25% são nativas de Curitiba, 24,83% são espécies nativas do Brasil e 24,83% são espécies exóticas. Encontraram-se 13 espécies exóticas invasoras: Citrus limon, Eriobotrya japonica, Eucalyptus grandis, Eucalyptus robusta, Eucalyptus viminalis, Eucalyptus sp., Hovenia dulcis, Ligustrum lucidum, Melia azedarach, Morus nigra, Pinus elliottii, Pinus sp. e Pittosporum undulatum. Psidium guajava foi a única espécie nativa do Brasil considerada invasora no Paraná. O Passeio Público foi o parque com maior número de espécies exóticas invasoras, enquanto o Parque Municipal do Passaúna apresentou maior número de espécies nativas de Curitiba. Palavras-chave: Áreas verdes; espécies exóticas; espécies nativas. Abstract Invasive tree species in urban parks landscaping of Curitiba, PR. The aim of this study was to characterize the introduced tree species in landscaping of five urban parks of Curitiba, mainly concerning invasive species. Five parks were randomly selected: “Passeio Público”, “Parque Bacacheri”, “Parque São Lourenço”, “Parque Barigui” and “Parque Municipal do Passaúna”. The trees were identified according to the taxonomy and origin. 5525 trees were analyzed, 95.9% were identified at species level. From the analyzed population, 149 species were identified as well as 48 families. Only 7 families represent 50% of all families, with a predominance of Fabaceae (20.8%), and the largest number of families was found in “Parque São Lourenço”. In relation to the origin, 38.25% of trees are native of Curitiba, 24.83% are native of Brazil and 24.83% are exotic species. 13 invasive alien species had been found: Citrus limon, Eriobotrya japonica, Eucalyptus grandis, Eucalyptus robusta, Eucalyptus viminalis, Eucalyptus sp. Hovenia dulcis, Ligustrum lucidum, Melia azedarach, Morus nigra, Pinus elliottii, Pinus sp and Pittosporum undulatum. Psidium guajava was the only Brazil native species considered invasive in Paraná. The “Passeio Público” is the park with the highest number of invasive alien species, and the “Parque Municipal Passaúna” had the greatest number of native species of Curitiba. Keywords: Green areas; alien species; indigenous species.